The Problems of Teachers in the Lithuanian Press of 1918–1940 - Selenis, Valdas (History / Istorija, 2019)
This article deals with Lithuanian periodicals of the Lithuanian Republic in 1918–1940 which discussed problems of teaching staff during this period. Teachers often demanded of better living conditions in order to rise to higher official position but after the Great economical crisis teachers salaries were not restored in the former level. Situation was even worse because teachers in rural areas did not received any travel allowances or house rent and transport money while working in rural areas. Rural teachers were cut from such cultural centres like libraries and theatres.